Cultura jurídica y legislación contra ladrones antes del Código Penal de 1837. Una aproximación histórica al derecho penal republicano temprano en Colombia (1820-1836) - Toro Silva, Carlos Alberto (Derecho penal y criminología, 2020)
This article approaches the transitional criminal law between the Castilian-Indian legal order of the viceroyalty of New Granada and the repub-lican legal order, focusing on the legislation against thieves prior to the Penal Code of 1837. This legislation intended to solve the problem of thefts that had increased after Independence. Initially, during the Republic of Colombia, harsh punishment prevailed, while in the Republic of New Granada the legislation was more moderate. It is shown that the form and structure of these laws was still influenced by the legal culture of the viceroyalty, despite the changes in the penal discourse of the 1821 and 1832 constitutions, of an enlightened-liberal nature. At the same time that said legislation sought to solve a specific problem, debates continued on the Penal Code which, in 1837, would give rise to the na-tional codified law. This early penal policy also sought to improve punishment establishments, although without success. Thus, the fledgling state was still far from establishing a true penal system. For the research, various sources were used seeking to understand the legislation within its political and ideological context.